An Empirical Examination of the Determinants of Foreign Direct Investment: A Firm-Level Analysis for the Colombian Economy (2014)
We use a large firm level data set to investigate the determinants of foreign direct investment(FDI) in Colombia. We estimate econometric models for the determinants of the probabilitythat a firm receives FDI, as well as for the factors that help to explain the foreign share in afirm’s capital. The results show that firms listed on the stock market, involved in foreign tradeactivities, and operating in sectors with greater capital intensity are more likely to be recipientsof FDI. Also, the probability of a firm receiving FDI is directly related to its size.